2019
DOI: 10.1016/j.reth.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessing clinical implications and perspectives of the pathophysiological effects of erythrocytes and plasma free hemoglobin in autologous biologics for use in musculoskeletal regenerative medicine therapies. A review

Abstract: Autologous biologics, defined as platelet-rich plasma (PRP) and bone marrow aspirate concentrate (BMC), are cell-based therapy treatment options in regenerative medicine practices, and have been increasingly used in orthopedics, sports medicine, and spinal disorders. These biological products are produced at point-of-care; thereby, avoiding expensive and cumbersome culturing and expansion techniques. Numerous commercial PRP and BMC systems are available but reports and knowledge of bio-cellular form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 86 publications
0
39
0
Order By: Relevance
“…Red Blood Cells (RBCs) can be damaged as a result of high shear force during blood collection or during inadequate centrifugation process, so causing hemolysis with the release of hemoglobin and its degradation products, hemin and iron. The presence of these hemolytic-related products lead to several deleterious effects, such as radical oxygen reactions, endothelial disfunction, vascular endothelium damage, pro-inflammation response and tissue injury [90].…”
Section: Red Blood Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Red Blood Cells (RBCs) can be damaged as a result of high shear force during blood collection or during inadequate centrifugation process, so causing hemolysis with the release of hemoglobin and its degradation products, hemin and iron. The presence of these hemolytic-related products lead to several deleterious effects, such as radical oxygen reactions, endothelial disfunction, vascular endothelium damage, pro-inflammation response and tissue injury [90].…”
Section: Red Blood Cellsmentioning
confidence: 99%
“…RBC damage also causes the release of migration inhibitory factor (MIF), which has been recognized as a very strong inflammatory cytokine [90]. MIF concentration in whole blood is 1000-fold increased than in plasma.…”
Section: Red Blood Cellsmentioning
confidence: 99%
“…In fact, several studies have reported that an excessive concentration of platelets may have inhibitory effects on cell proliferation or differentiation in populations such as tenocytes or adipose tissue-derived stem cells. Thus, the optimal platelet concentration for an optimized function is considered two-to threefold compared to blood levels [34,35].…”
Section: Blood Fractionation and Platelet-rich Plasma Obtentionmentioning
confidence: 99%
“…The presence of erythrocytes in the PRP entails their own degradation processes such as hemolysis and eryptosis. As a result, products that promote inflammation and cellular stress are generated, which would hinder the beneficial action of PRP [38].…”
Section: Blood Fractionation and Platelet-rich Plasma Obtentionmentioning
confidence: 99%
“…Throughout the aspiration procedure, RBCs can be damaged as a result of high shear forces [108]. As a consequence, the RBC membrane will start to disintegrate, and hemolysis, with the release of PFH, will occur.…”
Section: Red Blood Cells and Hemolysismentioning
confidence: 99%